The first Ordovician trilobite from Brazil: The dalmanitid Mucronaspis and implications for the glacial Hirnantian in western Gondwana - Zabini, Carolina; Randolfe, Enrique Alberto; Rustán, Juan José; Teófilo, Gabriel; Ghilardi, Renato Pirani [UNESP]; Martins, Henrique Bazzo (Elsevier, 2025)
We report a phacopid trilobite Mucronaspis sp. (Dalmanitidae), a typically Hirnantian (latest Ordovician) taxon, which represents, in turn, the first Ordovician (and oldest) trilobite record in Brazil. Fossils are from the glacial dropstone-bearing mudstones of the Iapó Formation, in a stratigraphic section from the northern part of the Paraná Basin. The Iapó Formation was independently referred to as the Hirnantian based on ostracods from mudstones with dropstones, followed by mudstones without dropstones of the overlying Vila Maria Formation. Evidence suggests that the Ordovician/Silurian boundary is located around the (transitional) limit between both stratigraphic units. Previous records of Mucronaspis in western Gondwana include the Argentine Precordillera in the Andean region and the intracratonic settings of Paraguay in the southern part of the Paraná Basin. This latter region records the only known (earliest) Silurian record of the genus. The biostratigraphic distribution of Mucronapsis worldwide appears isochronous, although it is virtually restricted to the Hirnantian, an early Silurian refuge is recorded south of the Paraná Basin. Abundant either in clear glacial or post-glacial settings, Mucronaspis appears to be an exceptionally tolerant eurytopic taxon, survivor of the first major mass extinctions.